Kontribusi Retribusi Daerah terhadap Pendapatan Asli Daerah (PAD) Kota Palangka Raya - Alexandro, Rinto (Universitas Pendidikan Ganesha, 2020)
Palangka Raya City Government is able to explore, manage, and maximize the potential of existing resources in order to increase revenue from the Regional Original Revenue in Palangkaraya City. This research is quantitative in nature and the research sample is the reception of regional levies from 2013 to 2018. Based on the results of managing data, the contribution of regional levies to the original income of the City of Palangkaraya is fluctuating, because the revenue from the area of regional levies experiences ups and downs in the income received, where the highest income was obtained in 2013 at 17.04% of the total Regional Original Revenue, and the lowest was obtained in 2018 at 11%.